New marker genes found in cassava - Hershey, Clair H.; Ocampo Nahar, César H. (1989)
Five new marker genes in cassava are described; they control the following traits: chlorophyll production in seedlings, stem growth habit, stem collenchyma color, root parenchyma color, and leaf lobe shape (pandurate vs. normal). Names were proposed for each loci and dominant and recessive phenotypes described. In the case of parenchyma color, the dominant gene appears to have a dosage effect, resulting in more intense color in the homozygote as compared with the heterozygote. Pandurate leaf shape presents some unclear segregation patterns, suggesting epistatic effects of other genes. Reciprocal crosses studied for segregation of seedling albinism, stem collenchyma color, and root parenchyma color show identical ratios regardless of which parent was male or female, indicating that inheritance is not influenced by cytoplasmic effects. (CIAT)